(untitled) (International journal of medical sciences, 2026)
This article analyzes modern approaches to endoscopic and radiological diagnosis of gastrointestinal diseases in children. Age-specific anatomical and physiological characteristics in pediatric patients necessitate the use of safe and minimally invasive diagnostic technologies. The diagnostic significance of gastroesophagoscopy, colonoscopy, capsule endoscopy, as well as ultrasonography, magnetic resonance imaging (MRI), and computed tomography (CT) is discussed. Integration of these diagnostic methods has been shown to improve diagnostic accuracy and contribute to the development of individualized treatment strategies.